2013
DOI: 10.2478/jppr-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Trichoderma Hamatum for Biocontrol of Lentil Vascular Wilt Disease: Efficacy, Mechanisms of Interaction And Future Prospects

Abstract: Trichoderma hamatum (Bonord.) Bainier was evaluated for its antagonistic potential against Fusarium oxysporum Schlecht. emend. Snyder and Hansen sp. lentis, the causal agent of vascular wilt disease of lentil (Lens culinaris Medikus). Hyphal interactions on Petri plates resulted in an increase in the number of conidial spores and an increase in the vegetative growth of T. hamatum, and a decrease in the hyphal formation and sporulation of F. oxysporum f. sp. lentis. Electron and light microscopical observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 45 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…The antagonistic mechanisms of Trichoderma against phytopathogens are in agreement with the mechanism reported by earlier researchers. El‐Hassan et al () also reported that biocontrol of Fusarium oxysporum f. sp. lentis using Trichoderma hamatum was associated with production of antifungal enzymes, complex mechanisms of mycoparasitism, and decreased hyphal formation and sporulation of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antagonistic mechanisms of Trichoderma against phytopathogens are in agreement with the mechanism reported by earlier researchers. El‐Hassan et al () also reported that biocontrol of Fusarium oxysporum f. sp. lentis using Trichoderma hamatum was associated with production of antifungal enzymes, complex mechanisms of mycoparasitism, and decreased hyphal formation and sporulation of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi are well known for their plant growth‐promoting traits and inducing protection against biotic and abiotic stress. They deter potential pathogens by inducing chemical responses of their hosts or by directly inhibiting colonization via interference competition (El‐Hassan et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial separation of T. hamatum and P. cap sici established the systemic nature of resistance induction in cucumber (Khan et al 2004). Trichoderma hamatum efficiently controlled vascular wilt disease of lentils caused by Fusarium oxysporum (El-Hassan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the rhizospheric symbiont AM fungi not only increases the nutrient uptake efficiency of most agricultural crops but are also known to increase soil structure and suppress diseases (Ziedan et al, 2011;Verbruggen et al, 2013). The saprophytic symbiont Trichoderma species are also associated with the plant roots which help in growth promotion and inhibition of important plant diseases (Hohmann et al, 2011;El-Hassan et al, 2013). As AM fungi is interacting with most rhizospheric organisms, the interaction studies between AM fungi and Trichoderma species has received positive attentions whose species number is still increasing (Doley and Jite, 2012a;Tanwar et al, 2013;Yabuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%